2023
DOI: 10.24875/gmm.m20000330
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in Mexican patients with common variable immunodeficiency

Abstract: Introduction: Common variable immunodeficiency (CVID) is the main symptomatic primary immunodeficiency and is associated with complex immune disorders. Gut microbiota interacts closely with the immune system, and intestinal dysbiosis is related to multiple diseases. Objective: To describe for the first time the composition of gut microbiota in Mexican patients with CVID. Methods: Fecal samples from five patients with CVID were collected and massive sequencing of the V3-V4 region of 16S rRNA gene was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Evidence suggested that Verrucomicrobia , as the few easily detected phylum in human intestine, had the function of maintaining the integrity of intestinal epithelial barrier and secreting antimicrobial peptides [ 65 ]. Furthermore, as the only known species of Verrucomicrobia that exists in human intestine, Akkermansia muciniphila 's abundance in UC patients decreased [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggested that Verrucomicrobia , as the few easily detected phylum in human intestine, had the function of maintaining the integrity of intestinal epithelial barrier and secreting antimicrobial peptides [ 65 ]. Furthermore, as the only known species of Verrucomicrobia that exists in human intestine, Akkermansia muciniphila 's abundance in UC patients decreased [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with IBD exhibited a higher abundance of Firmicutes and Actinobacteria but a lower abundance of Verrucomicrobia than healthy subjects [20]. Furthermore, these microbiota composition patterns were similar in patients with common variable immunodeficiency, where higher amounts of proinflammatory phyla (Firmicutes, Actinobacteria, and Verrucomicrobia) were associated with intestinal dysbiosis [21]. These findings highlight the relevance of dietary habits in the relationship between the immune system and the intestinal microbiota.…”
Section: The Mexican Colorectal Cancermentioning
confidence: 63%
“…5 ) is representative of intestinal dysbiosis in these patients, which was previously mentioned in another research article. [ 49 ] In conclusion, in this pilot study, we have provided several hints that gut microbiota is closely related to allergy symptoms.…”
Section: Discussionmentioning
confidence: 86%